CD83 expression is essential for Treg cell differentiation and stability - Döbbeler, Marina; Koenig, Christina; Krzyzak, Lena; Seitz, Christine; Wild, Andreas; Ulas, Thomas; Bassler, Kevin; Kopelyanskiy, Dmitry; Butterhof, Alina; Kuhnt, Christine; Kreiser, Simon; Stich, Lena; et al. (JCI Insight, 2018)
Foxp3-positive regulatory T cells (Tregs) are crucial for the maintenance of immune homeostasis and keep immune responses in check. Upon activation, Tregs are transferred into an effector state expressing transcripts essential for their suppressive activity, migration, and survival. However, it is not completely understood how different intrinsic and environmental factors control differentiation. Here, we present for the first time to our knowledge data suggesting that Treg-intrinsic expression of CD83 is essential for Treg differentiation upon activation. Interestingly, mice with Treg-intrinsic CD83 deficiency are characterized by a proinflammatory phenotype. Furthermore, the loss of CD83 expression by Tregs leads to the downregulation of Treg-specific differentiation markers and the induction of an inflammatory profile. In addition, Treg-specific conditional knockout mice showed aggravated autoimmunity and an impaired resolution of inflammation. Altogether, our results show that CD83 expression in Tregs is an essential factor for the development and function of effector Tregs upon activation. Since Tregs play a crucial role in the maintenance of immune tolerance and thus prevention of autoimmune disorders, our findings are also clinically relevant.
EVALuna2:36212

CD83 Modulates B Cell Activation and Germinal Center Responses - Krzyzak, Lena; Seitz, Christine; Urbat, Anne; Hutzler, Stefan; Ostalecki, Christian; Glaesner, Joachim; Hiergeist, Andreas; Gessner, Andre; Winkler, Thomas; Steinkasserer, Alexander; Nitschke, Lars (Journal of Immunology, 2016)
CD83 is a maturation marker for dendritic cells. In the B cell lineage, CD83 is expressed especially on activated B cells and on light zone B cells during the germinal center (GC) reaction. The function of CD83 during GC responses is unclear. CD83(-/-) mice have a strong reduction of CD4(+) T cells, which makes it difficult to analyze a functional role of CD83 on B cells during GC responses. Therefore, in the present study we generated a B cell-specific CD83 conditional knockout (CD83 B-cKO) model. CD83 B-cKO B cells show defective upregulation of MHC class II and CD86 expression and impaired proliferation after different stimuli. Analyses of GC responses after immunization with various Ags revealed a characteristic shift in dark zone and light zone B cell numbers, with an increase of B cells in the dark zone of CD83 B-cKO mice. This effect was not accompanied by alterations in the level of IgG immune responses or by major differences in affinity maturation. However, an enhanced IgE response was observed in CD83 B-cKO mice. Additionally, we observed a strong competitive disadvantage of CD83-cKO B cells in GC responses in mixed bone marrow chimeras. Furthermore, infection of mice with Borrelia burgdorferi revealed a defect in bacterial clearance of CD83 B-cKO mice with a shift toward a Th2 response, indicated by a strong increase in IgE titers. Taken together, our results show that CD83 is important for B cell activation and modulates GC composition and IgE Ab responses in vivo.

CD83 orchestrates immunity toward self and non-self in dendritic cells - Wild, Andreas; Krzyzak, Lena; Peckert, Katrin; Stich, Lena; Kuhnt, Christine; Butterhof, Alina; Seitz, Christine; Mattner, Jochen; Grner, Niklas; Gänsbauer, Maximilian; Purtak, Martin; Soulat, Didier; et al. (JCI Insight, 2019)
Dendritic cells (DCs) are crucial to balance protective immunity and autoimmune inflammatory processes. Expression of CD83 is a well-established marker for mature DCs, although its physiological role is still not completely understood. Using a DC-specific CD83-conditional KO (CD83(Delta DC)) mouse, we provide new insights into the function of CD83 within this cell type. Interestingly, CD83-deficient DCs produced drastically increased IL-2 levels and displayed higher expression of the costimulatory molecules CD25 and OX40L, which causes superior induction of antigen-specific T cell responses and compromises Treg suppressive functions. This also directly translates into accelerated immune responses in vivo. Upon Salmonella typhimurium and Listeria monocytogenes infection, CD83(Delta DC) mice cleared both pathogens more efficiently, and CD83-deficient DCs expressed increased IL-12 levels after bacterial encounter. Using the experimental autoimmune encephalomyelitis model, autoimmune inflammation was dramatically aggravated in CD83(Delta DC) mice while resolution of inflammation was strongly reduced. This phenotype was associated with increased cell influx into the CNS accompanied by elevated Th17 cell numbers. Concomitantly, CD83(Delta DC) mice had reduced Treg numbers in peripheral lymphoid organs. In summary, we show that CD83 ablation on DCs results in enhanced immune responses by dysregulating tolerance mechanisms and thereby impairing resolution of inflammation, which also demonstrates high clinical relevance.
CRIS-Team WoS Importer:2019-11-01

Murine CD83-positive T cells mediate suppressor functions in vitro and in vivo - Kreiser, Simon; Eckhardt, Jenny; Kuhnt, Christine; Stein, Marcello F.; Krzyzak, Lena; Seitz, Christine; Tucher, Christine; Knippertz, Ilka; Becker, Christoph; Günther, Claudia; Steinkasserer, Alexander; Lechmann, Matthias (Immunobiology, 2015)
The CD83 molecule (CD83) is a well-known surface marker present on mature dendritic cells (mDC). In this study, we show that CD83 is also expressed on a subset of T cells which mediate regulatory T cell (Treg)-like suppressor functions in vitro and in vivo. Treg-associated molecules including CD25, cytotoxic T lymphocyte antigen-4 (CTLA-4), glucocorticoid-induced TNFR family-related gene (GITR), Helios and neuropilin-1 (NRP-1) as well as forkhead box protein 3 (FOXP3) were specifically expressed by these CD83(+) T cells. In contrast, CD83(-) T cells showed a naive T cell phenotype with effector T cell properties upon activation. Noteworthy, CD83(-) T cells were not able to upregulate CD83 despite activation. Furthermore, CD83(+) T cells suppressed the proliferation and inflammatory cytokine release of CD83(-) T cells in vitro. Strikingly, stimulated CD83(+) T cells released soluble CD83 (sCD83), which has been reported to possess immunosuppressive properties. In vivo, using the murine transfer colitis model we could show that CD83(+) T cells were able to suppress colitis symptoms while CD83(-) T cells possessed effector functions. In addition, this CD83 expression is also conserved on expanded human Treg. Thus, from these studies we conclude that CD83(+) T cells share important features with regulatory T cells, identifying CD83 as a novel lineage marker to discriminate between different T cell populations.
EVALuna2:1841

Soluble CD83 inhibits skin inflammation to chemical sensitizers - Mihatsch, P.; Boyd, P.; Krzyzak, Lena; Lechmann, Matthias; Nicolas, J.; Mahler, Vera; Steinkasserer, Alexander; Vocanson, Marc (2016)
EVALuna2:26037

The CD83 molecule expressed by dendritic cells is a checkpoint to regulate resolution of inflammation as well as homeostasis within periphery and CNS - Wild, Andreas; Krzyzak, Lena; Mattner, Jochen; Winkler, Thomas; Nitschke, Lars; Steinkasserer, Alexander (2018)
EVALuna2:36214

Thymic CD4 T cell selection requires attenuation of March8-mediated MHCII turnover in cortical epithelial cells through CD83 - Von Rohrscheidt, Julia; Petrozziello, Elisabetta; Nedjic, Jelena; Federle, Christine; Krzyzak, Lena; Ploegh, Hidde L.; Ishido, Satoshi; Steinkasserer, Alexander; Klein, Ludger (Journal of Experimental Medicine, 2016)
Deficiency of CD83 in thymic epithelial cells (TECs) dramatically impairs thymic CD4 T cell selection. CD83 can exert cell-intrinsic and -extrinsic functions through discrete protein domains, but it remains unclear how CD83's capacity to operate through these alternative functional modules relates to its crucial role in TECs. In this study, using viral reconstitution of gene function in TECs, we found that CD83's transmembrane domain is necessary and sufficient for thymic CD4 T cell selection. Moreover, a ubiquitination-resistant MHCII variant restored CD4 T cell selection in Cd83(-/-) mice. Although during dendritic cell maturation CD83 is known to stabilize MHCII through opposing the ubiquitin ligase March1, regulation of March1 did not account for CD83's TEC-intrinsic role. Instead, we provide evidence that MHCII in cortical TECs (cTECs) is targeted by March8, an E3 ligase of as yet unknown physiological substrate specificity. Ablating March8 in Cd83(-/-) mice restored CD4 T cell development. Our results identify CD83-mediated MHCII stabilization through antagonism of March8 as a novel functional adaptation of cTECs for T cell selection. Furthermore, these findings suggest an intriguing division of labor between March1 and March8 in controlling inducible versus constitutive MHCII expression in hematopoietic antigen-presenting cells versus TECs.
EVALuna2:26036